β,β-Dimethylacrylshikonin Induces Mitochondria Dependent Apoptosis through ERK Pathway in Human Gastric Cancer SGC-7901 Cells - Shen, Xiu-Jin (Public Library of Science, 2012)
β,β-Dimethylacrylshikonin, one of the active components in the root extracts of Lithospermum erythrorhizon, posses antitumor activity. In this study, we discussed the molecular mechanisms of β,β-dimethylacrylshikonin in the apoptosis of SGC-7901 cells. β,β-Dimethylacrylshikonin reduced the cell viability of SGC-7901 cells in a dose- and time-dependent manner and induced cell apoptosis. β,β-Dimethylacrylshikonin treatment in SGC-7901 cells down-regulated the expression of XIAP, cIAP-2, and Bcl-2 and up-regulated the expression of Bak and Bax and caused the loss of mitochondrial membrane potential and release of cytochrome c. Additionally, β,β-dimethylacrylshikonin treatment led to activation of caspases-9, 8 and 3, and cleavage of poly (ADP-ribose) polymerase (PARP), which was abolished by pretreatment with the pan-caspase inhibitor Z-VAD-FMK. β,β-Dimethylacrylshikonin induced phosphorylation of extracellular signal-regulated kinase (ERK) in SGC-7901 cells. U0126, a specific MEK inhibitor, blocked the ERK activation by β,β-dimethylacrylshikonin and abrogated β,β-dimethylacrylshikonin -induced apoptosis. Our results demonstrated that β,β-dimethylacrylshikonin inhibited growth of gastric cancer SGC-7901 cells by inducing ERK signaling pathway, and provided a clue for preclinical and clinical evaluation of β,β-dimethylacrylshikonin for gastric cancer therapy.